Hybrid Synchronization of Lorenz-Stenflo System with Delay - Khan, Mohammad Ali (Journal of Advanced Computer Science & Technology, 2012)
This paper presents the hybrid-synchronization between two hyperchaoticLorenz-Stenflo system with delay. Here we design active controllersso that two pairs of states are synchronized and other two pairof states are anti-synchronized. Numerical results verify that both synchronizationand anti-synchronization can co-exist in the hyperchaoticLorenz stenflo system.